Environmental impact study of the Conga mining project - Pinto Herrera, Honorio (2014)
This work is an approach to Environmental Impact Assessment (EIA) Conga Mining Project (PMC). e main topics are: geographic location, denition of the EIA exposed PMC hired two supplements, the approval of the same and the reviews of several specialists. ey are two positions: 1) e defending Minera Yanacocha and 2) defending his critics that is more in line with reality.